2022
DOI: 10.3390/jcdd9090287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lower- versus Higher-Intensity Isometric Handgrip Training in Adults with Hypertension: A Randomized Controlled Trial

Abstract: This study compared the effects of lower- versus higher-intensity isometric handgrip exercise on resting blood pressure (BP) and associated clinical markers in adults with hypertension. Thirty-nine males were randomly assigned to one of three groups, including isometric handgrip at 60% maximal voluntary contraction (IHG-60), isometric handgrip at 30% IHG-30, or a control group (CON) that had been instructed to continue with their current activities of daily living. The volume was equated between the exercise g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Unfortunately, there are otherwise limited data on longitudinal adherence to IET, which remains a fundamental gap in the current literature. Data from short-term studies have reported good adherence to IET [64,66,73,77,80,84,85]. Palmeira et al [71] demonstrated an immediately concerning dropout rate of 50%; however, this value was similar to that observed in the control group (48%), which indicates factors other than IET (e.g., difficulty attending exercise sessions, city traffic, etc.)…”
Section: Duration and Adherencementioning
confidence: 96%
See 3 more Smart Citations
“…Unfortunately, there are otherwise limited data on longitudinal adherence to IET, which remains a fundamental gap in the current literature. Data from short-term studies have reported good adherence to IET [64,66,73,77,80,84,85]. Palmeira et al [71] demonstrated an immediately concerning dropout rate of 50%; however, this value was similar to that observed in the control group (48%), which indicates factors other than IET (e.g., difficulty attending exercise sessions, city traffic, etc.)…”
Section: Duration and Adherencementioning
confidence: 96%
“…Although numerous trials have consistently demonstrated the effectiveness of these intensities, comparative studies investigating novel protocols of variable intensity and inter-set recovery periods are needed to truly determine the optimal IET intensity prescription for the largest magnitude of effect on BP. Javidi et al [66] recently compared the traditional handgrip 30% MVC protocol (4 × 2 min) versus a novel 60% MVC protocol (8 × 30-s contractions), reporting significant resting BP reductions following both protocols, with significantly greater dBP reductions in the 60% MVC group. This work may provide promise for higher intensity, shorter contraction time IET protocols and ultimately highlights the importance of continued research into unexplored protocol variations.…”
Section: Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…Difference in muscle volume involved did not seem to matter, because isometric resistance training of the arm has been reported to show superior effects on SBP reduction compared to that of leg (−6.9 vs. −4.2 mmHg) [4]. Recently, Javidi et al compared the hypotensive effects between groups performing isometric handgrip at 60% (IHG-60) and at 30% (IHG-30) of maximum voluntary contraction (MVC) [10]. The volume was equated between the exercise groups, with IHG-60 performing 8 × 30 s contractions and IHG-30 performing 4 × 2 min contractions/day.…”
mentioning
confidence: 99%